Use of the Moodle Platform in English Language Learning in a Public University - Salazar Torres Torres, Martha Anabelle (2024)
Currently, English language teaching is one of the priorities of the curricular system; particularly in the Ecuadorian university environment, the English language is presented as a basic need for adequate professional development with a B1 level of proficiency. Moodle is a platform developed to manage educational material and support training processes through the Internet, ideal for educational institutions. Thus, teaching through the use of the Moodle platform is identified as a matter of interest and benefit to promote self learning of students. The different online learning strategies bear fruit when the teacher acts as a facilitator so that the students can acquire content that lasts over time. The methodology of the study is related to content analysis, i.e., the research of reliable bibliographic sources in recognized bases. In the study process, greater autonomy and independence are observed in the students when using the educational digital platforms for the development of their learning process. As a result, in this modular program, the student has access to the Moodle virtual platform where he/she can work autonomously and monitor the skills required for the development of the language.